HUBUNGAN VO2 MAX DAN POWER OTOT TUNGKAI TERHADAP KECEPATAN RENANG GAYA DADA 50 METER PADA MAHASISWA PUTRA IKIP MATARAM SEMESTER GENAP TAHUN AKADEMIK 2016/2017 - Dadang Warta Candra Wira Kusuma; Maulidin Maulidin; Adi Suriatno (Lembaga Penelitian dan Pendidikan Mandala, 2017)
This research is motivated by the water sports activities, especially in swimming that has huge demands in terms of theory and practice in the learning process so that the ideas and thoughts of the intellectuals are indispensable in the development process. This study aimed to determine the correlation between VO2 max and limb muscle power toward the 50 meters breaststroke swimming speed on male students at the IKIP Mataram in the second semester of academic year 2016/2017. This study is a correlation research. It used three variables consisting of two independent variables (VO2 max and limb muscle power) and one the dependent variable (breaststroke swimming speed). The population used in this study was all male students of IKIP Mataram at the second semester of academic year 2016/2017. To facilitate the data analysis, the researcher used purposive sampling techniques based on criteria that such samples were taken as many as 30 students. The data analysis used multiple correlation analysis with significance level of 5%. The results indicate that (1) there was a significant correlation of VO2 max variable toward the 50 meters breaststroke swimming speed on male students at the IKIP Mataram in the second semester of academic year 2016/2017, it was 0.427 (2) there was no significant correlation of variable limb muscle power toward the 50 meters breaststroke swimming speed on male students at the IKIP Mataram in the second semester of academic year 2016/2017, it was 0.294 (3) there was no correlation between VO2 max and limb muscle power on male student of IKIP Mataram in the second semester of academic year 2016 / 2017, it was 0.091 (4) there was a significant correlation between VO2 max and limb muscle power to the 50 meters breaststroke swimming speed on male students at the IKIP Mataram in the second semester of academic year 2016/2017, it was 0.497